Self-serving regret: experimental evidence from a reciprocity game - Zeng Lian; Xin Shen; Jie Zheng (Humanities & Social Sciences Communications)
Abstract Self-serving bias is a pervasive tendency in human behavior. Our study aimed to explore its manifestations in belief formation and the resulting behavior by using a three-stage reciprocity game that incorporated belief elicitation and regret option (N = 256). Specifically, we examined the post-decision regret of the recipients (reciprocators). The asymmetry between upward and downward adjustments by the reciprocators indicates a self-serving pattern: Reciprocators who underestimated the allocated amount are less likely to make an upward adjustment compared to the likelihood of a downward adjustment made by those who overestimated the allocated amount. This behavioral pattern is robust in both estimation and allocation biases, and across both extensive and intensive margins. Additionally, we investigated whether individuals form self-serving beliefs to justify their selfish actions but find no statistical evidence supporting this notion. Together, these findings contribute to the literature on self-serving bias by providing a lens to view beliefs and regret better.